Segmenting 20 Types of Pollen Grains for the Cretan Pollen Dataset v1 (CPD-1) - Nikos Tsiknakis; Elisavet Savvidaki; Sotiris Kafetzopoulos; Georgios Manikis; Nikolas Vidakis; Kostas Marias; Eleftherios Alissandrakis (Applied Sciences, 2021)
Pollen analysis and the classification of several pollen species is an important task in melissopalynology. The development of machine learning or deep learning based classification models depends on available datasets of pollen grains from various plant species from around the globe. In this paper, Cretan Pollen Dataset v1 (CPD-1) is presented, which is a novel dataset of grains from 20 pollen species from plants gathered in Crete, Greece. The pollen grains were prepared and stained with fuchsin, in order to be captured by a camera attached to a microscope under a <semantics>×400</semantics> magnification. In addition, a pollen grain segmentation method is presented, which segments and crops each unique pollen grain and achieved an overall detection accuracy of 92%. The final dataset comprises 4034 segmented pollen grains of 20 different pollen species, as well as the raw data and ground truth, as annotated by an expert. The developed dataset is publicly accessible, which we hope will accelerate research in melissopalynology.